CSS and HTML web design - Grannell, Craig (Friends of ED, 2007)
Includes bibliographical references (p. 504-506) and index; "A modern, modular approach to standards-compliant web design"--Cover; An Apress Company; An introduction to web design -- We page essentials -- Working with type -- Working with images -- Using links and creating navigation -- Tables: how nature (and the W3C) intended -- Page layouts with CSS -- Getting user feedback -- Dealing with browser quirks -- Putting everything together -- XHTML reference -- Web color reference -- Entities reference -- CSS reference -- Browser guide -- Software guide